Analysis of clinical and heart rate variability parameters associated with single-vessel and multivessel coronary artery disease: A retrospective study - Mingfang Zhu; Sixin Xie; Gang Lv; Xiang Zhang; Ding Peng (Pakistan Journal of Medical Sciences, 2026)
Objectives: To compare heart rate variability (HRV) parameters and cardiac biomarkers between patients with single-vessel and multivessel coronary artery disease (CAD) and assess their associations with multivessel involvement. Methodology: This retrospective study included 196 patients with angiographically confirmed CAD admitted between September 2022 and May 2025 at Ningguo People’s Hospital. Patients were classified as having single-vessel (n=55) or multivessel (n=141) disease. Group differences were assessed, and logistic regression was used to examine associations of SDNN, deceleration capacity (DC), high-sensitivity cardiac troponin T (hs-TnT), and N-terminal pro-B-type natriuretic peptide (NT-proBNP) with multivessel disease. Restricted cubic spline analysis explored potential nonlinear relationships. Results: The multivessel group had lower SDNN, SDANN, SDNN index, and DC and higher hs-TnT and NT-proBNP levels than the single-vessel group (all P